Ancestor Worship in China: Origin, Forms and Meaning - Karpińska, Wiktoria (Roczniki Kulturoznawcze, 2023)
Worshiping the spirits of departed ancestors is an essential element of traditional Chinese beliefs. As time passed, these beliefs underwent many transformations, but the cult of the dead remained a fundamental pillar of Chinese culture, linking the beliefs of the Chinese people from the Neolithic to the present. Thanks to Confucianism, it developed significantly and gained a new meaning, thanks to which it has a significant influence on Chinese society to this day. This article presents the origin and development of ancestor worship, indicates the role of Confucianism in its development, as well as discusses the most important feasts in honor of the dead and funeral rites. In addition, the author drew attention to the political dimension and place of ancestor worship in Chinese culture to this day.